A Psychodynamic Interpretation of Gender Differences in Descriptions of Religious Visions - Kavan, Heather (The international journal of religion and spirituality in society, 2013)
This paper offers a psychodynamic interpretation of descriptions of the visions of 112 Pentecostal and Charismatic Christians. Interviews and questionnaires were used to gather the data. The responses included experiences of visual and auditory perceptions and strong feelings of an immaterial presence. Almost one third of the visual and auditory perceptions were of Jesus. There were strong gender differences in the narratives, with women tending to describe interactive, nurturing and intercessory visions, infused with images of suffering and consolation, while men’s visions often related to powerful forces and danger. The analysis shows evidence of subconscious uprisings of suppressed material, projections mirroring the respondents’ psyches, wish fulfillment, and externalizations of the participants’ ideals. I suggest that visions reflect the fusion of the participants’ personal narratives and social roles with altered states of consciousness. The findings are consistent with the continuity hypothesis in psychological studies of dreaming (that waking-life gender differences carry over into dreams) and indicate this hypothesis can be extended to include visions.